ISLAM DAN AKHLAK - Muhammad Nawir; Imrayani; Hamsina H (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Contemporary educational challenges are becoming increasingly complex due to the widespread decline in moral conduct among students, reflected in various behavioral issues ranging from rudeness to minor criminal actions. This situation requires a comprehensive examination of the application of Islamic moral values in the educational context, particularly at Madrasah Aliyah Muhammadiyah Enrekang. This research aims to examine the essential relationship between Islamic principles and character building in the educational realm, map the methods of implementing Islamic moral values in modern learning systems, and develop an appropriate formula to shape students with noble character. The methodology used is qualitative, based on literature research, analyzing primary references from the Quran and Hadith, supported by academic sources such as scientific literature, research journals, and related publications. Data processing is done through content analysis with systematic stages, including data selection, information organization, and formulation of conclusions. The research findings indicate a significant relationship between the internalization of Islamic values and the development of moral character. In addition, an integrated approach to instilling Islamic moral values yields optimal results through a combination of three methods: providing direct exemplars, forming positive habits, and intensive guidance. This study also emphasizes that the success of character building depends on the synergy between educational institutions, family environment, and social communities, as well as the ability to adapt to technological advances.